Neutrophil Elastase Induces Chondrocyte Apoptosis and Facilitates the Occurrence of Osteoarthritis via Caspase Signaling Pathway - Ganyu Wang; Weiqiang Jing; Yuxuan Bi; Yue Li; Liang Ma; Hui Yang; Yuankai Zhang (Frontiers Media S.A., 2021)
Osteoarthritis (OA) is the most common and prevalent chronic joint disorders in the elderly population across the globe, resulting in severe disability and impairment of quality of life. Existing treatment can only alleviate the symptoms and delay the progression of OA. Therefore, novel and effective therapeutics strategies for OA need to be developed. Our present study first found that neutrophil elastase (NE) was significantly increased in OA patients' synovial fluid. Next, we examined the effect of neutrophil elastase (NE) on chondrocytes in vitro and in vivo. The results showed that NE suppressed cell proliferation, induced apoptosis and prevented cell migration in chondrocytes in vitro, accompanied by the elevation of intracellular ROS and calcium level. Moreover, NE enhanced the cleaved caspase-3 levels and disrupted the mitochondrial transmembrane potential balance. Meanwhile, chondrocytes apoptosis induced by NE can be alleviated by caspase inhibitor, zVAD-FMK and antioxidants, GSH. Besides, treatment of sivelestat, the inhibitor of NE, significantly reduced the pathological processes in OA model rats in vivo. The results of our study suggested that NE is an important factor in OA, which induces chondrocyte apoptosis and facilitates the occurrence of OA via caspase signaling pathway, and targeting the crucial signal centering around NE may be the potential therapies for OA.